THE POLITICAL COMMUNICATION AND THE ROMANIAN REGIONALISATION REFORM PROPOSAL OF 2013 – A DOUBLE DISCOURSE? / DIE POLITISCHE KOMMUNIKATION UND DER RUMÄNISCHE REGIONALISIERUNGSREFORMVORSCHLAG VON 2013 – EIN DOPPELTER DISKURS? - SĂLĂGEANU, Romana (Studia Universitatis Babes-Bolyai Studia Europaea, 2016)
The government programme of the government which started its mandate after the 2012 parliamentary election entailed a regionalisation and decentralisation reform, which was supposed to be a very large reform for Romania. However, the reform remained stuck in the communication process. This paper looks into whether the Romanian political actors pursued a double strategy by presenting different aspects of the reform to different actors. The first part of the paper entails a theoretical perspective on the political communication and the analysis frame. The second part presents the analysis that considers the following elements: the context of the reform, the pursued goals of the Romanian political actors and the receiver-actors towards who the communication took place. Therefore, the paper explains the communication that took place with regard to the proposed regionalisation reform from 2013, which has been further postponed.